New insight on the enteric cholinergic innervation of the pig colon by central and peripheral nervous systems: reduction by repeated loperamide administration - Yuan, Pu-Qing; Li, Tao; Million, Mulugeta; Larauche, Muriel; Atmani, Karim; Bellier, Jean-Pierre; Taché, Yvette (Frontiers in Neuroscience, 2023)
Introduction The central and peripheral nervous systems provide cholinergic innervation in the colon. The ability to assess their neuroanatomical distinctions is still a challenge. The pig is regarded as a relevant translational model due to the close similarity of its enteric nervous system (ENS) with that of human. Opioid-induced constipation is one of the most common side effects of opioid therapy. Methods We developed an approach to differentiate the central and peripheral cholinergic innervation of the pig colon using double immunolabeling with a novel mouse anti-human peripheral type of choline acetyltransferase (hpChAT) antibody combined with a rabbit anti-common type of ChAT (cChAT) antibody, a reliable marker of cholinergic neurons in the central nervous system. We examined their spatial configurations in 3D images of the ENS generated from CLARITY-cleared colonic segments. The density was quantitated computationally using Imaris 9.7. We assessed changes in the distal colon induced by daily oral treatment for 4 weeks with the μ opioid receptor agonist, loperamide (0.4 or 3 mg/kg). Results The double labeling showed strong cChAT immunoreactive (ir) fibers in the cervical vagus nerve and neuronal somata and fibers in the ventral horn of the sacral (S2) cord while hpChAT immunoreactivity was visualized only in the ENS but not in the vagus or sacral neural structures indicating the selectivity of these two antibodies. In the colonic myenteric plexus, dense hpChAT-ir neurons and fibers and varicose cChAT-ir fibers surrounding hpChAT-ir neurons were simultaneously visualized in 3D. The density of cChAT-ir varicose fibers in the outer submucosal plexus of both males and females were higher in the transverse and distal colon than in the proximal colon and in the myenteric plexus compared to the outer submucosal plexus and there was no cChAT innervation in the inner submucosal plexus. The density of hpChAT in the ENS showed no segmental or plexus differences in both sexes. Loperamide at the highest dose significantly decreased the density hpChAT-ir fibers + somata in the myenteric plexus of the distal colon. Discussion These data showed the distinct density of central cholinergic innervation between myenteric and submucosal plexuses among colonic segments and the localization of cChAT-ir fibers around peripheral hpChAT neurons in 3D. The reduction of cholinergic myenteric innervation by chronic opiate treatment points to target altered prokinetic cholinergic pathway to counteract opiate constipation.